Addition of phytogenic blend in different nutrient density diets of meat-type ducks. Issue 1 (1st January 2018) - Mohammadi Gheisar, Mohsen; Zhao, Pinyao; Kim, In Ho
ABSTRACT: A total of 160 1-d-old ducklings (mixed gender) were used to evaluate the effects of dietary phytogenic supplementation on growth performance, carcass characteristics, and nutrient digestibility. Each treatment consisted of eight replications and five birds/replication. Treatments were: (T1) high nutrient diet; (T2) T1+phytobiotics; (T3) low nutrient diet; (T4) T3+phytobiotics. The results indicated that inclusion of phytobiotics and nutrients' density of diets influenced body weight gain and feed conversion ratio ( P  < .05). Feeding low nutrient diets had a negative effect on drip loss percentage. Cooking loss percentage increased ( P  < .05) by reducing nutrient density. Relative weights of breast muscle, abdominal fat and body organs, pH value, and colour of breast muscle were not affected by treatment diets. Supplementing the diets reduced TBARS value on d 14 post-slaughter ( P  < .05). Density of nutrients and phytogenic blend ( P  < .05) improved the digestibility of dry matter and energy, but the digestibility of calcium and phosphorous were not affected by treatments.